Willingness to Pay Pelayanan Konseling Apoteker di Apotek di Kecamatan Polokarto Tahun 2016 - Harlianti, Mariska Sri; Andayani, Tri Murti; Puspandari, Diah Ayu (Universitas Muhammadiyah Surakarta, 2018)
Counseling is one part of the clinical pharmacy service at the pharmacy that is the responsibility of the pharmacist to achieve therapeutic goal. Community needs for counseling have increased so that the active participation of pharmacists is needed through the provision of professional services. This research needs to be done to find out the amount of counseling services by pharmacists who are willing to be paid by patients with a WTP (Willingness to Pay) value parameter. In addition, the value of WTP can also describe the indirect benefits felt by the community towards counseling services by pharmacists at the pharmacy. This research is a descriptive observational research through a survey. The study was conducted at the pharmacy in the Polokarto sub-district of Sukoharjo regency in January – February 2016 with pharmacy visitor respondents who received counseling services by pharmacists. A total of 82 patients participated in this study. The amount of WTP is determined based on the average WTP value chosen by the patients with the payment card method. The result showed that the average WTP value of pharmacist counseling services at pharmacies in Sukoharjo regency was Rp. 15,892.